Implementation of the independent curriculum for students with special needs at SDN Gadang 03 Malang City - Salsabillah, Ana Nur; Suwandayani, Beti Istanti; Nuro, Falistya Roisatul Mar'atin (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to find out how the independent curriculum was implemented for students with special needs at SD Gadang 3 Malang City as well as the types of children with special needs within it. Data collection techniques used in this study include interviews, observations, and documentation. The subjects of this research are 5th-grade teachers who also handle students with special needs, the school principal, and the students with special needs themselves. Data analysis techniques used are data collection, data reduction, data display, and verification. The results of this study indicated that the implementation of the independent curriculum for students with special needs at SDN Gadang 3 is packaged in a simple and detailed manner. So both regular and those with special needs, can effectively and maximally absorb the delivered material. There is no specific strategy in the learning process, it's just that the method of delivery uses diction that is easy to understand. The use of teaching modules in the learning process is also generalized to other students. The process of assessing learning outcomes is obtained from the mid-semester and final-semester examinations provided by the GPK team in their respective cities.